Practice, Knowledge, and Awareness of the Diverse Effects of Diagnostic Radiology among Radiology Staff and Students in Saudi Arabia - Alyahyawi, Amjad; Elasbali, Abdelbaset M.; Ahmed, Hussain Gadelkarim (Current Medical Imaging, 2022)
Background: Diagnostic radiology has been linked to several health consequences. Thus, the present study aimed to assess the practice, knowledge, and awareness of the diverse effects of diagnostic radiology among radiology staff and students in Saudi Arabia. Methodology: In this study, 107 participants were recruited from August to December 2020. The study included 56 radiology personnel (staff from Hail City Hospitals) and 51 radiology medical students (students from the University of Ha’il). Results: To the question, “Have you ever been informed of radiation and its effects?” about 6/107 (5.6 %) answered “No,” among which 5/6 (83.3 %) were the staff. In response to the question, “In your opinion, how hazardous is radiation to your body?” about 8/104 (7.7 %) indicated it as nonhazardous (3 were staff and 5 were students). To the question, “Do you believe that radiation in medical sites is harmful?” about 20/104 (19.2 %) answered, “No” (8 were staff and 12 were students). Conclusion: There is a lack of awareness, knowledge, and practice towards ionizing radiation protection measures among radiology medical students and radiology department staff in Northern Saudi Arabia. The paper notifies the health system advisors to include stressing guidelines regarding radiation hazards. More actions are deemed necessary for the safety of patients and radiation workers.
Keywords: radiology